Venography and Selective Ablation for Recurrent Varices after Surgery Using Radiofrequency Ablation Catheter. (11th March 2021) - Enta, Yusuke; Saigan, Makoto; Tanaka, Akiko; Hata, Masaki; Tada, Norio
Abstract : Recurrent varices after surgery (REVAS) is a common problem with no established treatment. Ultrasonography is a hard method to identify the source of veins that cause REVAS, especially in obese patients with thick thighs. Here, we report the case of a 64-year-old obese patient who previously underwent endothermal venous ablation for her right great saphenous vein. The patient presented with right leg swelling and venous ulceration due to REVAS. Although the source of REVAS was unclear because the patient had thick thighs on ultrasonography assessment, venography revealed that the source of REVAS was the incompetent perforator vein (IPV). Selective ablation for the IPV with radiofrequency ablation catheter was performed. We could ablate the target veins selectively so as not to ablate within the deep vein. The patient remains asymptomatic for 2 years after the procedure, and there has been no recurrence of her varicose veins. Venography allows better visualization of the source of REVAS than ultrasonography. With selective ablation, it is especially effective procedure in obese patients, in whom it is difficult to identify and access the source of REVAS with ultrasonography.